PELATIHAN PENYUSUNAN KONTEN PEMASARAN DIGITAL BERBANTUAN ARTIFICIAL INTELLIGENCE (AI) BAGI PELAKU UMKM DI KOTA SERANG - Irma Nurmala Dewi; Khaeruman Khaeruman; Jaka Wijaya Kusuma; Tabroni Tabroni; Hafidz Hanafiah (Yayasan Education and Social Center, 2026)
The rapid development of digital technology has encouraged Micro, Small, and Medium Enterprises (MSMEs) to adopt more adaptive and innovative marketing strategies. However, many MSME actors still face challenges in creating attractive and effective Digital marketing content. This community service activity aimed to improve the capacity of MSME actors in Serang City through training on Digital marketing content development assisted by Artificial Intelligence (AI). The program was conducted for one month in November 2025 using participatory methods consisting of lectures, demonstrations, hands-on practice, mentoring, and evaluation. A total of 40 MSME participants from the culinary, fashion, handicraft, and service sectors attended the training. The results indicated significant improvements in participants’ understanding of Digital marketing, AI utilization, content creation skills, and digital promotion strategies. Participants were able to create promotional captions, product descriptions, social media content plans, and visual marketing materials using AI-based applications. The training also enhanced participants’ creativity, efficiency, and confidence in implementing Digital marketing strategies. Furthermore, the activity contributed to strengthening digital literacy and supporting business competitiveness in the digital economy era. Therefore, AI-assisted Digital marketing training can serve as an effective empowerment strategy for improving MSME performance and sustainability.